Diary of a Conference in Moscow March 1991 - Saul, Norman (Journal of Russian American Studies, 2020)
This article is a reprint of historian Norman Saul’s diary and offers a vivid, firsthand account of his experiences during a March 1991 conference in Moscow, set against the backdrop of the Soviet Union’s transition from communism to a market economy. The text captures both the personal and professional dimensions of the journey, reflecting on the practical challenges of daily life, the political climate surrounding Gorbachev’s referendum, and the dynamics of academic exchanges. Saul’s observations illuminate the tensions of a society in flux, blending anecdotal detail with broader commentary on Russian-American relations and the evolving roles of historical scholarship amid systemic upheaval.